Overexpression of NK4 gene in TU212 affects migratory activity in laryngeal squamous cell carcinoma - Huo, Yixuan; Zhang, Wei; Yang, Fan; Shao, Wenhua; Cong, Guozheng; Zhang, Shoukai (Frontiers in Oncology, 2025)
BackgroundAbnormal activation of the hepatocyte growth factor (HGF) and c-mesenchymal–epithelial transition factor (c-Met) signaling pathway is associated with tumor occurrence and development. Serum HGF concentrations are significantly higher in patients with advanced and poorly differentiated laryngeal squamous cell carcinoma than those with early and highly differentiated disease. NK4, a splice variant of HGF, can competitively bind to c-Met and acts as a specific antagonist of HGF. Although preliminary research has been conducted on the tumor-suppressing function of the NK4 gene, its specific mechanism of action in laryngeal cancer remains unclear.MethodsStable laryngeal squamous cell carcinoma cell lines expressing NK4 were developed using a lentiviral packaging method. The experimental group was labeled with PLV-NK4-TU212, whereas the control group was labeled with PLV-NC-TU212. Western blotting verified a stable expression. The functions of the NK4 molecule were assessed using MTT, EMT, and apoptosis assays, and cell lines were subjected to transcriptome sequencing.ResultsProtein expression analysis showed that NK4 was stably expressed. Compared with the wild-type and negative control groups, overexpression of the NK4 gene inhibited the migration and proliferation of laryngeal squamous cell carcinoma cells and induced cell apoptosis. Transcriptome sequencing revealed that the expression levels of 320 genes differed significantly, with 189 upregulated and 131 downregulated genes.ConclusionIn this study, a TU212 laryngeal squamous cell carcinoma cell line overexpressing NK4 was constructed using a lentiviral packaging system. Functional experiments showed that PLV-NK4-TU212 cells exhibited a significantly reduced migration rate, decreased proliferative ability, and increased apoptosis rate. The results of this study provide an experimental basis for NK4 as a potential therapeutic target for laryngeal squamous cell carcinoma highlighting its translational medical value.